2013
DOI: 10.1038/nrneph.2013.98
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism in the pathogenesis of iron-induced kidney injury

Abstract: In the past 8 years, there has been renewed interest in the role of iron in both acute kidney injury (AKI) and chronic kidney disease (CKD). In patients with kidney diseases, renal tubules are exposed to a high concentration of iron owing to increased glomerular filtration of iron and iron-containing proteins, including haemoglobin, transferrin and neutrophil gelatinase-associated lipocalin (NGAL). Levels of intracellular catalytic iron may increase when glomerular and renal tubular cells are injured. Reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 123 publications
5
123
1
Order By: Relevance
“…It has also been shown that AKI increases intracellular levels of free catalytic iron, which increases oxidative stress and renal injury after IR-AKI (35). Moreover, acetaminophen, which inhibits iron-catalyzed lipid peroxidation (7), attenuates serum and/or urinary isofuran/F2-isporsotane levels in patients with sepsis (27), and in patients undergoing cardiopulmonary bypass surgery (5,51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that AKI increases intracellular levels of free catalytic iron, which increases oxidative stress and renal injury after IR-AKI (35). Moreover, acetaminophen, which inhibits iron-catalyzed lipid peroxidation (7), attenuates serum and/or urinary isofuran/F2-isporsotane levels in patients with sepsis (27), and in patients undergoing cardiopulmonary bypass surgery (5,51).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other antioxidants, PM can scavenge different toxic RCS, including lipid peroxidation products (59,61), which contribute to tissue injury under conditions of oxidative stress (37,49). In addition, PM can sequester redox metal ions, including free iron, and inhibit their ability to catalyze multiple toxic oxidative pathways (35,58,60). Because PM therapy targets multiple oxidative reactions in vivo, in particular redox-active metal ions that amplify pathological stress responses, the beneficial effects of PM may occur at lower effective drug concentrations compared with those of antioxidants, like vitamin E and NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo in the steady state, absorbed iron is exported to the interstitium and capillary blood across the basolateral (BL) membrane of PT cells (6 -8). The transport of iron between different body, cell, and subcellular compartments is complicated because the known membrane transporters for iron (8) accept only the more soluble ferrous form (Fe 2ϩ ), whereas the majority of iron in the extracellular fluid and serum is in the more stable ferric form (Fe 3ϩ ) bound to either transferrin (Tf) or small molecules (non-Tf bound iron or NTBI). Hence, there is a need for iron redox enzymes close to the site of membrane transport (see Fig.…”
Section: Prion Protein (Prpmentioning
confidence: 99%
“…A similar reaction is likely to occur under pathological conditions when NTBI and/or hemin filtered through the glomeruli come in contact with PrP C on the plasma membrane of PT cells (8). To evaluate this possibility, PT cells expressing PrP C or PrP ⌬51-89 were exposed to hemin or FAC overnight, and lysates were subjected to Western blotting and probed for PrP and ␤-actin (Fig.…”
Section: ⌬51-89mentioning
confidence: 99%